Transcatheter Aortic Valve Replacement in the Presence of Mitral Prosthesis or Ring. Issue 2 (4th March 2019) - Biton, David; Grossman, Yoni; Finkelstein, Ariel; Assali, Abid; Halkin, Amir; Brodov, Yafim; Fefer, Paul; Barbash, Israel M.; Goitein, Orly; Landes, Uri; Arbel, Yaron; Guetta, Victor; et al.
ABSTRACT: Background: Data concerning transcatheter aortic valve replacement (TAVR) in patients with prior mitral surgery is limited and preliminary reports seem encouraging. We sought to describe TAVR outcomes in the presence of mitral prosthesis. Methods: Clinical, imaging and angiographic records of patients with previous mitral valve surgery who underwent TAVR in three Israeli tertiary hospitals were analyzed. Amongst the patients, 28 received a balloon-expandable valve, nine received a self-expandable valve, and one received a mechanically-expandable valve. Aorto-mitral distance and angle were obtained from reconstructed multi-sliced CT images. Primary endpoint was a composite of procedural mortality, need for a second valve, complete AV block, significant paravalvular leak (PVL), and intensive care unit (ICU) admission > 5 days. Results: Thirty-eight patients (74% women) with a mean age of 76 ± 7 years underwent TAVR. Euroscore2 and Society of Thoracic Surgeons (STS) score were 12 ± 9% and 6 ± 5%, respectively. Mean aorto-mitral distance was 9 ± 1 mm and aorto-mitral angle was 117 ± 14°. Mean TAVR implantation depth was 6.1 ± 3 mm. The composite end-point occurred in 15.8% of patients (n = 6), driven by need for a second valve (n = 1), and by three patients that underwent valve snaring due to mitral valve impingement, complete aortic valve (AV) block, and PVL. The 90-day and 1-year mortality was 8% and 21%, respectively. A statistically significant association (HR = 11.2, 95%CI 2.8–45.5, p = 0.012) was found between low implantation depth (>8 mm) and the composite end-points. Conclusion: TAVR in the presence of mitral valve prosthesis adds to the complexity of the procedure and promotes higher procedural risk. Meticulous pre-procedural anatomic assessment and patient selection are mandatory. Implantation depth of less than 8 mm seems prudent.